KEMAMPUAN INTERAKSI SOSIAL SISWA DAN PENGEMBANGANNYA OLEH GURU BIMBINGAN DAN KONSELING - Indah Waraswita; Suhendri (Universitas Muhammadiyah Metro, 2024)
The main focus in this research is students' social interaction abilities and their development by supervising teachers at SMA Negeri 5 Semarang. In interacting, many things are discovered, both negative and positive. This shows that interaction is an ability that is learned in the process of everyday life. This ability to interact can be developed through guidance and counseling services, as implemented at SMA Negeri 5 Semarang. The method the author uses in this research is a descriptive method. In this research the author carried out observations, interviews and documentation to obtain the required data. Based on the research that the author has conducted, it can be concluded that: First, in adapting to the social environment, there are students who are capable and there are those who are unable. Students who are unable to adapt are generally less able to interact in the social environment of SMA Negeri 5 Semarang. Second, to find close friends, there are students who are able to get them and those who are not. Students who are unable to find close friends are those who are unable to adapt, have been traumatized by previous close friends, are less open and are less able to interact. Third, there are students who are able to create a sense of self-confidence when studying and there are also those who are not. Self-confidence does not arise due to factors within and outside the individual. Fourth, the efforts made by supervising teachers to develop students' ability to adapt, to build closeness and create self confidence is by providing counseling guidance services both in the personal and social fields by supervising teachers at SMA Negeri 5 Semarang